IDENTIFIKASI KARAKTERISTIK FISIKOKIMIA YOGHURT NABATI DENGAN PENAMBAHAN PUREE BUAH NIPAH (Nypa fruticans) - Zuhair Abdullah; Caca Pratiwi; Esi Emilia; Risti Rosmiati; Erni Rukmana (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2026)
Plant-based yogurt made from coconut milk has potential as an alternative to dairy yogurt for individuals with lactose intolerance while promoting the utilization of local food resources. This study aimed to evaluate the physicochemical, microbiological, and antioxidant characteristics of coconut milk yogurt supplemented with nipa palm fruit (Nypa fruticans) puree. An experimental study was conducted using a Completely Randomized Design with three puree concentrations (20%, 25%, and 30%). Parameters analyzed included fat content, non-fat solids, protein, ash content, pH, titratable acidity, viscosity, Total Plate Count (TPC), and antioxidant activity using the DPPH method. Data were analyzed using one-way ANOVA followed by Duncan’s New Multiple Range Test at a 5% significance level. The addition of nipa palm fruit puree did not significantly affect fat, non-fat solids, protein, ash, pH, or acidity, but significantly influenced viscosity, TPC, and antioxidant activity. Increasing puree concentration tended to enhance viscosity and antioxidant activity; however, TPC values did not meet the national yogurt standard. Coconut milk yogurt enriched with nipa palm fruit puree shows potential as a functional food product based on local ingredients.